THE IMPACT OF CHLORIN WATER ON THE DEVELOPMENT OF DENTAL CARIES AMONG PEOPLE IN LINGKUNGAN DASAN CERMEN UTARA IN 2015 - Dian Paramita; Sufie Haswinda; Hazizah - (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Chlorin calsium is solid white substance which is ready to be decomposide in water to subsequently release oxygen and chlorin. Basd on the research result, chlorin water contibutes to the riskof dental caries development. Dental caries caused by chlorin water starts with demineralization on the email layer. Email becomes fragile and will develop cavity on the dental surface. The objective of this studyis to identify the impact of the chlorin water towards the development of dental caries in Lingkungan Dasan Cermen Utara in 2015.This research is comparative study with a sampled 50 respondens. The tecnique of sampling is simple random sampling. The methode for data collection used is questionnares and intra oral examinations. The location of the study was among the people of Lingkungan Dasan Cermen Utara.The data analysis used SPSS independent sample t-test. The finding shows significance as seen from the sigma value of 0.00 which lower than 0.05.The conclusion is that there is a significant different of impact between those people using chlorin water who are more vulnarable to dental caries than those using deep well water.